(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
This article explores the multifaceted concept of space in Toni Morrison’s Beloved through a postcolonial ecocritical lens, focusing on how natural and domestic spaces serve as sites of memory, trauma, and healing for African American characters in the aftermath of slavery. The study examines three key spaces—the Ohio River, Baby Suggs’ Clearing, and the haunted house at 124 Bluestone Road—as symbolic realms where the characters navigate their fractured identities and confront the lingering ghosts of their past. The Ohio River emerges as a liminal space of rebirth and emancipation, while the Clearing represents a communal sanctuary for spiritual and emotional healing. The haunted house, on the other hand, embodies the inescapable past, where the trauma of slavery continues to haunt the present. Through these spaces, Morrison not only critiques the environmental and psychological scars of colonialism but also highlights the resilience and agency of her characters as they seek to reclaim their histories and identities. This article argues that Morrison’s portrayal of space in Beloved underscores the interconnectedness of human and non-human worlds, offering a profound commentary on the enduring impact of slavery and the possibility of redemption through nature and community.